The Development of Piano Curriculum Construction for Master of Arts in Colleges and Universities under the Guidance of Career - Bing, Fang; Xiao Mei, Liang (Journal of Roi Kaensarn Academi, 2024)
The cultivation of high-end piano talents has always been the ultimate goal of piano education in colleges and universities, so the curriculum optimization and construction around piano talent training has also become the focus of academic discussion. High-quality piano curriculum is the basis and guarantee for colleges and universities to achieve the goal of cultivating piano master of art talents, so the comprehensive teaching curriculum construction is carried out from all aspects of piano professional basic training, cultural literacy edification and practical level development. only in this way can we ensure the characteristics of the curriculum construction of piano major in colleges and universities, and highlight the effectiveness of the curriculum of piano majors in colleges and universities. However, the construction of the professional curriculum of the Master of Piano Arts in colleges and universities is a lasting exploration problem, which needs to be constantly tested and improved by the majority of teaching staff in the practice of piano curriculum. in order to form a systematic and professional piano curriculum system. In the research of this paper, combined with my own experience in piano curriculum development, from the aspects of the concept of piano curriculum, the construction of curriculum system, the integration of teaching curriculum, the construction of curriculum teaching module and the expansion of curriculum practice, this paper makes a series of discussions on the curriculum construction of piano major in colleges and universities, in order to train more high-quality practical piano talents for the society.